Jacek Kochanowicz – profesor Uniwersytetu Warszawskiego - Leszczyńska, Cecylia (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
Jacek Kochanowicz – Professor of the Warsaw University (Summary) The article presents the person of Professor Jacek Kochanowicz, one of the most distinguished Polish economic historians of the past few decades. It discusses the role he played as a scholar, a teacher of generations of students of the Warsaw University and a lecturer at a number of foreign universities, highlighting the way in which he understood economic history – a discipline to which he devoted his scholarly life.